PROFILE OF FARMERS OF SWADAYA PALM IN KAYONG UTARA - Rahimin - Rahimin; Dewi Kurniati; Maswadi Maswadi (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT This research is based on the increasing area of oil palm plantation cultivated in Kayong Utara. Thus increasing employment opportunities for the community in Kayong Utara. The purpose of this study was to determine the factors that influence the level of work productivity of independent oil palm farmers in North Kayong Regency. The population in this study were independent oil palm farmers in North Kayong District, with a total of 71 respondents. The analysis used is multiple linear regression. The results of this study are that the variables of Education, Work Experience variables and Other Income variables proved to have a significant influence on the work productivity of independent / independent oil palm farmers in Seponti District, North Kayong Regency. Keyword: oil palm, independent oil palm plantations, work productivity.